Türkiye Country Climate and Development Report - World Bank Group (Washington, DC: World Bank, 2022)
Integrating climate and development is a pillar of the World Bank Group’s Climate Change Action Plan 2021-25. To advance its implementation, the Bank Group has launched a new, core diagnostic tool: the Country Climate and Development Report, a new, core diagnostic tool that analyzes how a country’s development goals can be achieved in the context of adapting to and mitigating against climate change. These reports will reflect the country’s climate commitments and identify ways to support their implementation through public and private sector solutions. They will capture the centrality of people in policies on climate change adaptation and mitigation, assessing how climate risks affect people, and ways in which governments can build resilience and address poverty, distributional and job impact of climate change and climate action. The Turkiye Country Climate and Development Report explores how climate action, in line with the country’s mitigation goal of achieving net zero emissions by 2053 as well as its adaptation and resilience needs, interact with its growth and development path and contribute to achieving the country’s development objectives, help seize opportunities offered by green technologies, protect the economy against longer-term risks such as large-scale disasters or carbon lock-in as the world transitions towards zero-carbon technologies, and support a just and inclusive transition for all.